A quantum dot-based fluorescence sensor for sensitive and enzymeless detection of creatinine. Issue 30 (15th July 2016) - Tajarrod, Narjes; Rofouei, Mohammad Kazem; Masteri-Farahani, Majid; Zadmard, Reza
Abstract : A schematic illustration of a sensitive creatinine probe using fluorescence enhancement of water-soluble thioglycolic acid capped ZnS:Mn/ZnS core/shell quantum dots. Abstract : In this paper, we report a novel "turn-on" fluorescence sensor for selective and sensitive determination of creatinine (Crn) in human serum and urine samples, using thioglycolic acid (TGA) capped ZnS:Mn/ZnS quantum dots (QDs). TGA capped ZnS:Mn/ZnS QDs have been synthesized via a facile aqueous co-precipitation method and characterized by fluorescence, UV-vis absorption, Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), X-ray diffraction (XRD), dynamic light scattering (DLS) measurements and energy-dispersive X-ray spectroscopy (EDS). The fluorescence emission spectrum of TGA functionalized ZnS:Mn/ZnS QDs showed a significant increase in emission intensity in the presence of Crn. The enhancement in emission is due to passivation of the surface trap states of QDs through the binding of Crn with the QD surface, which results in the formation of new radiative electron–hole recombination centers. The interaction between Crn and QDs was investigated by some analytical techniques such as fluorescence, UV-vis spectroscopy and DLS measurements. Under the optimum conditions the probe offers a good linear relationship between 0.07 and 3.4 μM for Crn with the correlation coefficient ( R 2 ) of 0.9963 and limit of detection (LOD) and limit of quantification (LOQ) of 7.25 nM and 0.0242 μM, respectively. The method was successfully employed for the analysis of the Crn content in human serum and urine. The proposed method demonstrated several advantages such as high sensitivity, short analysis time, low cost and ease of operation.